Adobe Photoshop CS3 Beta First Look with Adobe Bridge and Camera Raw - Long, Ben, 1967- (Peachpit Press, 2007)
This book, covering the public beta of Photoshop CS3 will get you up to speed with the new interface changes, and will help you learn all of the new features in the CS3 beta such as next generation Camera Raw, new and improved Bridge, Photoshop Lightroom Integration, improved printing, Nondestructive smart filters, black and white conversion controls, improved curves, automatic Layer Alignment and Blending, and more. The Photoshop CS3 Beta is available free for download on Adobe labs for registered users of of either Photoshop CS2, Adobe Creative Suite 2 Standard or Premium, Adobe Production Studio Standard and Premium, Adobe Video Bundle or Adobe Web Bundle.